Enhancing cosmetology students’ communication skills in Malaysian upper secondary vocational education program - Tee Tze Kiong; Farah Najwa Ahmad Puad; Arasinah Kamis; Yee Mei Heong; Ruhiana Idayu Abd Hamid; Sharifah Shafie; Sarimah Abu Bedor (Institute of Advanced Engineering and Science, 2022)
The quality of beauty treatment services will be evaluated by the clients subjectively whether they are satisfied or otherwise with the services provided. However, the reports and complaints related to customer dissatisfaction when receiving beauty treatment services at beauty centers are increasing. Unfortunately, the suggestions for improvement from the previous studies are still insufficient. Therefore, this study was conducted to examine the importance of proficiency in communication skills and the need for training modules in the teaching and learning process (T&L). It is required to improve communication skills among cosmetology students for Upper Secondary Vocational Education Program (USVEP) in beauty arts course. The data were collected through the interview method on six USVEP teachers and a beauty salon entrepreneur. The findings of the study found that the proficiency in communication skills among the cosmetology students is an important requirement for employers in selecting their employees, increasing customer loyalty and the customer’s frequency to visit beauty salons, and maintaining the excellent performance of cosmetology students in the workplace. In addition, there is also a high demand for the development of communication skills training modules in helping cosmetology students to constantly updated with new knowledge and skills needed from time to time. Therefore, adequate training is required to improve the competency in communication skills among the cosmetology students.